Histopatologi Paru Dan Hati Pada Kasus Leucocytozoonosis Ayam Broiler - Daniel, Daniel; Wardhani, Lailia Dwi Kusuma; Hasan, M. (Universitas Islam Kadiri, 2024)
Leucocytozoonosis, known as Malaria Like Disease, is a blood protozoan disease from the genus Leucocytozoon sp. Three broiler chickens from Ampera Jaya Farm Aceh Besar. Chickens experience clinical symptoms of feathers that look dull, the skin on the feet has petechiae, the eye membranes are hyperemic (conjunctivitis), the nasal and oral cavities contain mucous exudate and green feces. Chicken blood is taken via the brachial vein in the wing to be used to observe blood smears. The chicken experienced sudden death and a necropsy was carried out and the lungs and liver were taken to make histopathological preparations. The research results showed that there was Leucocytozoon sp. in blood smear preparations and schizonts in liver and lung histopathology. So in cases of death of broiler chickens it is caused by infection from Leucocytozoon sp. which causes changes in the histopathology of the chicken's lungs and liver with the discovery of schizon Lungs, Liver, Leucocytozoonosis, Broiler chickens